Electrochemical performance of manganese hexacyanoferrate cathode material in aqueous Zn-ion battery. (20th December 2021) - Li, Min; Sciacca, Rosalinda; Maisuradze, Mariam; Aquilanti, Giuliana; Plaisier, Jasper; Berrettoni, Mario; Giorgetti, Marco
Highligths: Sodium manganese hexacyanoferrate show high specific capacity in aqueous Zn-ion battery. Fe-site was activated at beginning cycles owing to the dissolution of Mn-site. Zn-ions inserted to the Mn-site during cycling and forming Zn-N-C-Fe structure. XAS data indicate the Fe electro-activity. Abstract: Manganese hexacyanoferrate (MnHCF) has attracted much attention as promising cathode material for Li and Na ion batteries, owning to its low cost, environmental friendliness, high specific capacity and voltage plateau. Here, the electrochemical performance and electronic structure information of MnHCF were studied in aqueous Zn-ion batteries (ZIBs). Based on the cyclic voltammetry and galvanostatic charge/discharge results, an activation of Fe-sites during beginning cycles was observed, and the capacity contribution of Fe-sites increases from 30 to 86% at C/20 during the first 10 cycles. The local geometric and electronic structure information of MnHCF was investigated by X-ray absorption spectroscopy (XAS) in a set of ex-situ electrodes. From Fe K-edge spectra, it shows a consistent oxidation and reduced state in charged and discharged electrodes, and this indicates that there is no apparent change for the local Fe-sites environment. However, the XAS spectra of Mn K-edge show apparent change after 10 cycles. Compared to the rhombohedral phase of Zinc hexacyanoferrate (ZnHCF), a -Zn-CN-Fe- structural framework was detected in the cycled MnHCF samples, and this indicates that a part of Zn replaced Mn-sites, because of the dissolution of the Mn-sites. The gradual activation of Fe-sites at the beginning cycles can be attributed to the alleviation spatial resistance with the dissolution of Mn-sites, and the replacement of Zn for Mn explains the decreasing capacity during cycling.